Polymer nanocomposites in diabetes management: advances in biosensors and drug delivery systems - Aniruddha Sen (Discover Materials)
Abstract This review focuses on the latest advancements in polymer nanocomposites and their important role in the treatment of diabetes, namely in the fields of biosensors and drug delivery systems. Integrating nanoparticles into polymers has resulted in the development of glucose biosensors that exhibit increased sensitivity and selectivity, hence improving the accuracy of blood glucose monitoring. These technological improvements have made it easier to determine the exact amount of insulin needed and have improved the quality of clinical decisions, resulting in better treatment for individuals with diabetes. In addition, polymer nanocomposites have facilitated innovative drug delivery techniques that guarantee the continuous and regulated release of insulin and other antidiabetic drugs, thereby tackling the issue of maintaining consistent glycaemic levels. The review also examines how durable, biocompatible, and detrimental these nanocomposites are to the environment if we are to reach world goals for sustainability. Examining current research trends, clinical applications, and future possibilities, our paper explores how polymer nanocomposites can enable individuals with diabetes to perform better.